• 2022-05-27
    设f(x)=2x,则f″(x)=()
    A: 2x·ln22
    B: 2x·ln4
    C: 2x·2
    D: 2x·4
  • A

    内容

    • 0

      设 $f(\sin x)=\cos2x+1$,则 $f(\cos x)=$( ). A: $\cos^2x$ B: $-2\cos^2x$ C: $-2\sin^2x$ D: $2-2\cos^2x$

    • 1

      已知\( y = {x^3}\cos 2x \),则\( y'' \)为( ). A: 0 B: \( 6x\cos 2x{\rm{ + }}12{x^2}\sin 2x - 4{x^3}\cos 2x \) C: \( 6x\cos 2x - 12{x^2}\sin 2x{\rm{ + }}4{x^3}\cos 2x \) D: \( 6x\cos 2x - 12{x^2}\sin 2x - 4{x^3}\cos 2x \)

    • 2

      ‏随机变量X服从正态分布,则 也服从正态分布。‍ A: X+2 B: X^2 C: 2X D: ln(X) E: 2X+10 F: ln(X)-4

    • 3

      函数\(y = {e^{ - {x^2}}}\)的导数为( ). A: \( - 2x{e^{ - {x^2}}}\) B: \(2x{e^{ - {x^2}}}\) C: \( - 2x{e^ { { x^2}}}\) D: \(2x{e^ { { x^2}}}\)

    • 4

      函数\(y = {x^2} - \ln x\)的导数为( ). A: \(2x - {1 \over x}\) B: \(2x + {1 \over x}\) C: \( - 2x + {1 \over x}\) D: \( - 2x - {1 \over x}\)